2022
DOI: 10.3390/healthcare10061138
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity, Emotions and Health: The Role of Trust/Mistrust in God in People Affected by Cancer

Abstract: Trust in God implies the conviction that God looks after a person’s own interests. The first evidence of a relationship between this construct and people’s psychological and emotional health dates back several centuries. However, the literature on this is limited, especially for people with physical health conditions, such as cancer. Therefore, the purpose of this study is to test the relationships between trust/mistrust in God, social support and emotions in people affected by cancer. The sample consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Religiosity, spirituality, and social support have also been associated with a positive impact on the mental health well-being of these patients. For example, a study which examined the role of trust/mistrust in God in people affected by cancer reported that valuing the religiosity and spirituality of patients in health settings positively impacted the health of the patients [ 45 ] Research conducted in terminally ill AIDS patients in Uganda suggests that the existential/spiritual well-being domain was the most important [ 46 ]. Other studies in patients with metastatic disease have also demonstrated that this domain has potential for growth even in the face of advancing disease and declining function [ 47 ], and this may explain the importance of patient’s attachment to it.…”
Section: Discussionmentioning
confidence: 99%
“…Religiosity, spirituality, and social support have also been associated with a positive impact on the mental health well-being of these patients. For example, a study which examined the role of trust/mistrust in God in people affected by cancer reported that valuing the religiosity and spirituality of patients in health settings positively impacted the health of the patients [ 45 ] Research conducted in terminally ill AIDS patients in Uganda suggests that the existential/spiritual well-being domain was the most important [ 46 ]. Other studies in patients with metastatic disease have also demonstrated that this domain has potential for growth even in the face of advancing disease and declining function [ 47 ], and this may explain the importance of patient’s attachment to it.…”
Section: Discussionmentioning
confidence: 99%